How to report biogas production when monitoring small-scale digesters in field. (January 2016) - Martí-Herrero, J.; Flores, T.; Alvarez, R.; Perez, D.
Abstract: The aim of this research was to evaluate the error originated when biogas production from field monitoring digesters, influenced by the diurnal temperature cycle, was normalized to standard conditions for pressure and temperature (273.15 K and 100 kPa) from local conditions. The biogas production data is often reported without indicating if done under local conditions, whether these conditions have been standardized and, if they have actually been standardized, the standard temperature and pressure is not indicated. In this research ambient and biogas temperature, as well as biogas production were monitored with a 30 min frequency during three consecutive days, in three different tubular digesters. Normalization was realized using the high frequency data collected as reference values, and also using daily biogas production with mean daily biogas, ambient and nearby meteorological station temperatures. The outcome of this research shows that normalization of biogas production can be obtained using daily biogas production and the daily mean ambient temperature with an overestimation by no more than 1.5%, in comparison to the normalization achieved by using high frequency data from biogas temperature and production. Using mean daily ambient temperature or mean daily biogas temperature results in the same overestimation, while using mean daily ambient temperature from a nearby airport weather station pushes the overestimation up to 2.7%. So, if ambient temperature and altitude is identified, biogas production reported in local conditions can be normalized. Highlights: Normalization of biogas production from field monitored digesters was analyzed. Three tubular digesters were high frequency monitored during three consecutive days. 30 min biogas production and temperature profile were reported for each digester. Normalization of biogas production was done using different temperatures. For normalization proposes, daily mean ambient temperature was satisfactory.